2012
DOI: 10.1002/lsm.22007
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Low‐Level Laser Therapy for Noninvasive Body Contouring

Abstract: These data reveal that the circumferential reduction exhibited following LLLT is not attributable to fluid or fat relocation as all measurement points, including nontreated regions, reported an inch loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 29 publications
8
53
2
Order By: Relevance
“…On the other hand the results of the current study contradict the results of a studies done by Elm et al, (2011) [26]. As well as the study by Jackson and his coworkers in 2013 which investigated the efficacy of the ability of low-level laser therapy to improve the appearance of cellulite.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand the results of the current study contradict the results of a studies done by Elm et al, (2011) [26]. As well as the study by Jackson and his coworkers in 2013 which investigated the efficacy of the ability of low-level laser therapy to improve the appearance of cellulite.…”
Section: Discussioncontrasting
confidence: 99%
“…However, two weeks after the last treatment session, a 7.8-mm increase in circumferences was seen in three treated zones (62). In another clinical study, Jackson et al reported that treating 689 subjects with LLLT (12 treatment sessions within 14 days) leads to 13.13-cm circumferential reduction in waist, hips, thighs, arms, knees, neck and chest (63). …”
Section: Resultsmentioning
confidence: 99%
“…In addition, Jackson and colleagues [12] find changes in the body composition as in circumferential measurements across waist, hips, and thighs compared to placebo subjects after LLLT treatment, with a total of six treatments across 2-weeks. The authors suggest that change in the adipose tissue occurs due to adaptations in the membrane permeability of adipocytes, releasing fatty acids in blood circulation, but their removal and metabolism mechanisms still remain unclear [12].…”
Section: Introductionmentioning
confidence: 99%